Seed Priming and its Consequences on Seedling Vigour of Bell Pepper (Capsicum annuum L.) under Low Temperature Condition - Sharma, Nisha; Shukla, Y. R.; Mehta, D. K. (International Journal of Bio-resource and Stress Management, 2023)
Capsicum (Capsicum annuum L.) is an important vegetable crop grown worldwide. In Himachal Pradesh, the seeds of capsicum are generally sown during January-February for raising an off-season crop. The sub-optimal temperature results in slow and poor germination, sometimes causing decay of seeds. The problem of poor or slow germination can be solved through many techniques and one of them is priming. Seed priming is known to endow plants with greater tolerance to subsequent stress exposure of the same or different kind. During priming, the seeds are partially hydrated in such a way that pre-germination metabolic activities start, however, radicle protrusion is prevented followed by drying of seeds to the original moisture content. In the present studies, the effect of seed priming using different priming agents like PEG-6000, Gibberellic acid, KH2PO4,Na2HPO4, distilled water and cow urine was studied to see its effect on seedling vigour of bell pepper seeds. Seeds were primed at 20 °C for 24 and 48 hours to evaluate the effect on germination and seedling vigour. Results revealed that all priming treatments significantly improved seed performance over control. Seeds primed with GA3 at 100 ppm for 48 h excelled over all other treatments as this treatment decreased time taken to 50% germination, increased root and shoot length, seedling fresh weight and seedling vigour over all other priming treatments. In addition, the growth performance of the plants obtained from primed seeds was better than control, suggesting chemical seed priming as an eco-friendly approach for enhancing seed germination under low temperature conditions.